Satellite record of the transition of air quality over China. Issue 2 (3rd April 2018) - Chen, Liangfu; Tao, Minghui; Wang, Zifeng; Tao, Jinhua; Yu, Chao; Zhang, Ying; Fan, Meng; Gu, Jinabin; Su, Lin
ABSTRACT: The rapid development of atmospheric satellite instruments since 1990s provides unprecedented large amount of observational datasets concerning global atmospheric pollutants. The continuous and long-term large-scale satellite products such as aerosol optical depth, tropospheric NO2 and SO2 enable effective and objective evaluation of air quality. Satellite columnar aerosol optical parameters can be used to indicate particle pollution near surface after correction. By contrast, satellite results of trace gas pollutants such as NO2 and SO2 from fossil fuel combustion with short lifetime around half one day are used to estimate anthropogenic emissions. It is shown that the overall anthropogenic emissions in China have largely declined since strict emission reduction policy implemented since 2013. However, coarse pixel resolution of the trace gases, limited information and retrieval bias of aerosol properties tend to hinder further application of satellite in air quality research. Recently launched satellite missions with advanced detection abilities will greatly enhance global atmospheric observations with much more datasets available.